2019
DOI: 10.1002/mp.13370
|View full text |Cite
|
Sign up to set email alerts
|

MPEXS‐DNA, a new GPU‐based Monte Carlo simulator for track structures and radiation chemistry at subcellular scale

Abstract: PurposeTrack structure simulation codes can accurately reproduce the stochastic nature of particle–matter interactions in order to evaluate quantitatively radiation damage in biological cells such as DNA strand breaks and base damage. Such simulations handle large numbers of secondary charged particles and molecular species created in the irradiated medium. Every particle and molecular species are tracked step‐by‐step using a Monte Carlo method to calculate energy loss patterns and spatial distributions of mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 47 publications
(109 reference statements)
1
15
0
Order By: Relevance
“…It is based on the Geant4-DNA package and can also simulate chemical reactions and the diffusion process for molecular species, and the distribution of molecular species can also be determined. In this study [114], the authors confirmed that the simulation results, which were obtained using MPEXS-DNA, were consistent with existing experimental and simulation data. Compared with simulations that were performed in Geant4-DNA with a single CPU core, MPEXSDNA performed the same simulations thousands times faster, keeping the accuracy at the same level.…”
Section: Monte Carlo Techniques For Radiobiological Modellingsupporting
confidence: 89%
See 1 more Smart Citation
“…It is based on the Geant4-DNA package and can also simulate chemical reactions and the diffusion process for molecular species, and the distribution of molecular species can also be determined. In this study [114], the authors confirmed that the simulation results, which were obtained using MPEXS-DNA, were consistent with existing experimental and simulation data. Compared with simulations that were performed in Geant4-DNA with a single CPU core, MPEXSDNA performed the same simulations thousands times faster, keeping the accuracy at the same level.…”
Section: Monte Carlo Techniques For Radiobiological Modellingsupporting
confidence: 89%
“…A recent addition on simulating radiation chemistry and track structures at the subcellular scale is the MPEXS-DNA, GPU-based Monte Carlo simulator [114]. MPEXS-DNA uses the speed of GPU processing for the physical, physicochemical, chemical and biological stages of the simulation process of IR interaction with biological matter.…”
Section: Monte Carlo Techniques For Radiobiological Modellingmentioning
confidence: 99%
“…Another interesting example is reported by Okada et al [248], where a new MC simulator named MPEXS-DNA is described, allowing high computing performance by using a GPU. The code has been developed for track structure and radiolysis simulations at the subcellular scale.…”
Section: Gpu-based MC For Radiobiological Calculationsmentioning
confidence: 99%
“…A number of tools and computational platforms have been developed based on MC techniques by many researchers with varying degree of complexity. 2 Several MC packages have been proposed and/or studied for radiobiology calculations, such as MCDS 3 and DBSCAN, 4 which are based on MC simulations' results to calculate radiobiological parameters, and RADAMOL, 5 PAR-TRAC, 6 Geant4-DNA, 7,8 TRAX, 9,10 RITRACKS, [11][12][13] MPEXS-DNA, 14 TOPAS-nBio, 15,16 gMicroMC, 17,18 which are MC simulation codes. Recent studies, 7,8,[16][17][18][19][20] include specific DNA or cell models that can also simulate the early radiation-induced damage.…”
Section: Introductionmentioning
confidence: 99%